Corrosion-resistant and hydrogen embrittlement-resistant composite coating for titanium-based bipolar plate and preparation method thereof

By coating the surface of the titanium base bipolar plate with a titanium transition layer, a Magneli phase titanium suboxide hydrogen barrier layer, a titanium sealing layer and a precious metal conductive layer, a corrosion-resistant and hydrogen embrittlement-resistant composite coating is formed, which solves the problem of dual-stage PEM water electrolyzers. The plate is prone to corrosion and cathode hydrogen embrittlement in the corrosive environment of high anode potential and low pH value, but achieves efficient hydrogen barrier and conductive properties.

CN119352062AActive Publication Date: 2025-01-24SHANGHAI HESHENG CHUANGHE ENERGY TECH CO LTD

Patent Information

Application Number
CN202411896401.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-01-24
Estimated Expiration
2044-12-23

AI Technical Summary

Technical Problem

The PEM water electrolytic cell bipolar plate is prone to corrosion under high potential and low pH corrosion environment of the anode, and the passivation/oxidation of the anode metal material forms a large contact resistance with the gas diffusion layer. Hydrogen embrittlement is prone to occur in the cathode hydrogen environment, resulting in water electrolysis. Reduced efficiency.

Method used

Apply the titanium -to -bean bipolar plate surface to coat the titanium transition layer, MagneLi's titanium oxide hydrogen resistance, titanium seal layer and precious metal conductive layer, forming a composite coating of etching resistance and hydrogen.

Benefits of technology

It effectively blocks the diffusion and penetration of hydrogen, improves the anti-hydrogen embrittlement performance of the cathode side of the bipolar plate, reduces coating processing costs and process complexity, while ensuring corrosion resistance and conductive performance, and adapting to the high potential and low pH corrosion environment of the anode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119352062A_ABST
    Figure CN119352062A_ABST
Patent Text Reader

Abstract

The invention discloses a titanium base material bipolar plate corrosion-resistant and hydrogen embrittlement-resistant composite coating and a preparation method thereof. The surface of a titanium base material is sequentially coated with a titanium transition layer, a titanium black hydrogen resistance layer, a titanium hole sealing layer and a precious metal conducting layer; the titanium transition layer is an elemental titanium layer, and the thickness of the titanium transition layer is 10-30 nm; the material of the titanium black hydrogen blocking layer is Magneli-phase titanium black with the molecular formula of TinO2n-1, wherein n is greater than or equal to 4 and less than or equal to 10, and the thickness is 100-150nm; the titanium hole sealing layer is an elemental titanium layer, and the thickness of the titanium hole sealing layer is 10-50nm; the precious metal conducting layer is made of at least one of platinum, gold, ruthenium and iridium, and the thickness of the precious metal conducting layer is 20-50 nm. The corrosion-resistant and hydrogen embrittlement-resistant composite coating disclosed by the invention can effectively block diffusion and permeation of hydrogen in a cathode environment of a PEM water electrolyser while ensuring corrosion-resistant and conductive performance, so that the hydrogen embrittlement-resistant performance of the cathode side of the bipolar plate is greatly improved, and the processing cost and the process complexity of the coating are reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of bipolar plates for PEM water electrolyzers for producing hydrogen by water electrolysis, and specifically relates to a corrosion-resistant and hydrogen-embrittlement-resistant composite coating for titanium-based bipolar plates and a preparation method thereof. Background Art

[0002] Hydrogen is one of the most abundant elements in nature and plays an important role in energy and chemical industry, energy storage and power generation, food processing and other fields. Proton exchange membrane water electrolysis (PEM water electrolysis) is a green hydrogen production method that has developed rapidly in recent years. It has the advantages of high current density, high working efficiency and high hydrogen purity.

[0003] Hydrogen production by water electrolysis is essentially an energy conversion process of electricity to gas. The PEM water electrolyzer uses solid electrolytes to give it a zero-gap structure. This structure is more flexible and efficient than alkaline electrolyzers, but it also places higher requirements on the conductivity of components and the interface contact resistance between components. Precious metals (especially titanium) are the preferred coating materials for bipolar plates in PEM water electrolyzers due to their extremely excellent conductivity, high specific strength, corrosion resistance and chemical stability.

[0004] The cathode side of the PEM water electrolyzer is where the hydrogen evolution reaction occurs. However, since hydrogen atoms have the smallest atomic radius, they have a strong diffusion ability in metals. When the metal surface cannot effectively inhibit the dissociation of hydrogen molecules into atomic hydrogen (hydrogen atoms H, hydrogen ions H) + / H - ), hydrogen can easily penetrate into the metal material and dissolve in it. When hydrogen enters the metal material, it will reduce the tensile strength, fatigue strength and fracture toughness of the metal material, causing hydrogen embrittlement. Figure 2 This is a schematic diagram of the three stages of hydrogen dissolution in the hydrogen embrittlement phenomenon. The first stage is the reversible physical adsorption on the metal surface due to the van der Waals interaction between hydrogen molecules and the metal surface. In the second stage, chemical adsorption occurs after the dissociation of hydrogen molecules due to short-range chemical interactions and occurs within the single atomic layer. In the third stage, due to the existence of a hydrogen concentration gradient, atomic hydrogen diffuses into the interior of the metal material, that is, hydrogen penetration dissolution occurs.

[0005] The titanium substrate precious metal coating conventionally used for bipolar plates of PEM water electrolyzers cannot effectively inhibit the dissociation of hydrogen adsorbed on the cathode, resulting in poor hydrogen embrittlement resistance and high susceptibility to hydrogen penetration. It is generally believed that when the solubility of hydrogen in titanium exceeds several hundred ppm, the mechanical properties of titanium such as toughness and plasticity will be significantly reduced, and there is a risk of cracking under stress conditions.

[0006] In order to solve the hydrogen embrittlement problem, researchers usually apply platinum / gold and other precious metal coatings on the surface of titanium bipolar plates to ensure high conductivity and corrosion resistance, and to block the penetration of hydrogen on the cathode side. However, the single precious metal coating has limited resistance to hydrogen embrittlement. Hydrogen often penetrates the coating from the coating defects and invades the interior of the titanium substrate, causing hydrogen embrittlement. Increasing the thickness of the precious metal coating can form a dense coverage of the precious metal coating, thereby alleviating hydrogen penetration, but this will lead to an increase in the overall manufacturing cost of the electrolyzer.

[0007] Magneli phase titanium oxide is a compound with the molecular formula Ti n O 2n-1 A general term for non-stoichiometric titanium oxides (where 4≤n≤10). Magneli phase titanium oxide has the advantages of resistance to various acid and alkali corrosion, high electrochemical stability, and good electrical conductivity. It has been gradually applied to fuel cells, zinc-air batteries, lead-acid batteries, and sewage treatment.

[0008] Patent document CN110071302A discloses a titanium matrix sub-titanium oxide bipolar plate and its preparation method, wherein the titanium matrix is ​​placed in a micro-arc oxidation electrolyte for micro-arc oxidation treatment, and a carbon-containing titanium dioxide ceramic layer is grown in situ; the titanium matrix obtained after micro-arc oxidation treatment is then subjected to carbon thermal reduction treatment until the titanium dioxide ceramic layer on the surface of the titanium matrix is ​​converted into a sub-titanium oxide (Ti4O7) ceramic layer with conductive function. However, the titanium matrix sub-titanium oxide bipolar plate in this document is used for lead-acid flow batteries, and there is no precious metal conductive layer on the surface to protect it, so it cannot be used in PEM water electrolyzers. Summary of the invention

[0009] The purpose of the present invention is to provide a titanium substrate bipolar plate corrosion-resistant and hydrogen embrittlement-resistant composite coating and a preparation method thereof, so as to solve the following problems existing in the PEM water electrolysis bipolar plate in the prior art: ① large corrosion damage to metal materials in the harsh corrosive environment of high anode potential and low pH value; ② passivation / oxidation of anode metal materials, forming a large contact resistance with the gas diffusion layer; ③ hydrogen embrittlement of metal materials is prone to occur in the cathode hydrogen environment; ④ ion precipitation caused by corrosion or hydrogen embrittlement of anode and cathode metal materials, thereby poisoning the proton membrane and causing a decrease in water electrolysis efficiency.

[0010] The purpose of the present invention is achieved through the following technical solutions: The present invention discloses a titanium substrate bipolar plate corrosion-resistant and hydrogen embrittlement-resistant composite coating, wherein a titanium transition layer, a titanium suboxide hydrogen barrier layer, a titanium sealing layer and a noble metal conductive layer are sequentially coated on the surface of the titanium substrate; The titanium transition layer is a single titanium layer with a thickness of 10 to 30 nm; its function is to enhance the interface matching between the titanium substrate and the sub-titanium oxide hydrogen barrier layer and strengthen the film-base bonding force; The material of the titanium oxide hydrogen barrier layer is Ti n O 2n-1(where 4≤n≤10) Magneli phase titanium suboxide, the thickness of which is 100-150nm; its function is to improve the corrosion resistance and hydrogen embrittlement resistance of the titanium substrate without sacrificing the conductivity of the titanium substrate; the Magneli phase titanium suboxide is preferably Ti4O7, Ti5O9, Ti6O 11 One or more of the following: The titanium sealing layer is a single titanium layer with a thickness of 10 to 50 nm. Its function is to enhance the interface matching between the sub-titanium oxide hydrogen barrier layer and the noble metal conductive layer, and to seal and cover the pinholes, nodules and other through-type defects that may appear in the hydrogen barrier layer and the conductive layer, thereby preventing hydrogen from diffusing and penetrating from the coating defects to the inside of the substrate. The material of the noble metal conductive layer is at least one of platinum, gold, ruthenium and iridium, and the thickness is 20 to 50 nm; its function is to ensure corrosion resistance and conductivity and reduce the interface contact resistance between the titanium bipolar plate and the anode and cathode gas diffusion layers.

[0011] Preferably, the total thickness of the corrosion-resistant and hydrogen-embrittlement-resistant composite coating is 160 to 260 nm.

[0012] Preferably, the titanium-based bipolar plate is one of a pure titanium flat plate with a metal stretching / stamping mesh, a pure titanium plate with an etched flow channel, and a stamped pure titanium bipolar plate; preferably, the titanium-based bipolar plate is made of pure titanium material labeled TA1 or TA2, and preferably has a thickness of 0.5 to 2 mm.

[0013] The present invention also provides a method for preparing the corrosion-resistant and hydrogen-embrittlement-resistant composite coating of the titanium substrate bipolar plate, comprising the following steps: S1, titanium substrate pretreatment: first, the titanium substrate is polished step by step, then mirror polished, then ultrasonically cleaned in acetone and ethanol respectively, and dried with cold air; S2, composite coating preparation: depositing a titanium transition layer, a titanium suboxide hydrogen barrier layer, a titanium sealing layer and a noble metal conductive layer on the surface of the titanium substrate in sequence.

[0014] Preferably, the step-by-step grinding uses sandpaper with a mesh size of 400 to 1200, and the mirror polishing uses diamond grinding paste.

[0015] It should be noted that, although the present invention only takes magnetron sputtering as an example, the preparation process of the composite coating includes one or more physical vapor deposition methods such as magnetron sputtering, multi-arc ion plating and / or electron beam evaporation. The output mode of the magnetron sputtering power supply can also be one or more of direct current, direct current pulse and / or high power pulse; the pre-treated titanium substrate is placed in the sputtering deposition equipment, and the background vacuum of the deposition chamber is less than 1×10 -3The titanium transition layer and the titanium sealing layer use a titanium metal single substance target as a sputtering target; the titanium suboxide hydrogen barrier layer uses a Magneli phase titanium suboxide target as a sputtering target; and the noble metal conductive layer uses a noble metal single substance target as a sputtering target.

[0016] Preferably, before the composite coating is deposited, the surface of the titanium substrate needs to be etched with glow plasma, wherein the main component of the glow plasma is Ar ions, and the etching time is 20 to 60 minutes.

[0017] Compared with the prior art, the present invention has the following beneficial effects: The present invention adopts Magneli phase titanium oxide as the hydrogen barrier layer. Due to its unique lattice stacking structure, it has both conductive corrosion resistance and a low hydrogen diffusion coefficient. Compared with precious metal coatings, it has better hydrogen embrittlement resistance and better cost advantages. It ensures that the corrosion-resistant and hydrogen-embrittlement-resistant composite coating of the present invention can effectively block the diffusion and penetration of hydrogen in the cathode environment of the PEM water electrolyzer while ensuring corrosion resistance and conductive properties, greatly improving the hydrogen embrittlement resistance of the cathode side of the bipolar plate, and reducing the coating processing cost and process complexity.

[0018] Generally speaking, the coating of the bipolar plate will inevitably have defects such as droplets, pinholes, impurities, nodules, etc., and through-type defects such as pinholes and nodules will form favorable channels for hydrogen diffusion and penetration. The present invention adds a titanium sealing layer between the hydrogen barrier layer and the conductive layer, which not only further improves the overall hydrogen embrittlement resistance of the composite coating by sealing and covering the coating defects of both, but also enhances the interfacial bonding force between the compound hydrogen barrier layer and the elemental metal conductive layer, ensuring that the corrosion-resistant and hydrogen-embrittlement-resistant composite coating can withstand the harsh high-potential and low-pH corrosion environment of the anode of the PEM water electrolyzer, and has the same good conductivity and corrosion resistance as the pure precious metal coating.

[0019] The anode side and cathode side of the PEM water electrolyzer have different service environments. The anode side focuses on the requirements for the bipolar plate material to be conductive and corrosion-resistant, while the cathode side focuses on the requirements for the bipolar plate material to be conductive and resistant to hydrogen embrittlement. Since the corrosion-resistant and hydrogen-embrittlement-resistant composite coating of the present invention has both excellent conductive corrosion resistance and hydrogen embrittlement resistance, it is not necessary to adopt two different coating systems or coating processes on both sides of the bipolar plate of the present invention, which greatly reduces the process complexity of the bipolar plate coating. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 It is a schematic diagram of the corrosion-resistant and hydrogen-embrittlement-resistant composite coating of the titanium substrate bipolar plate of the present invention.

[0021] Figure 2 It is a schematic diagram of the three stages of hydrogen dissolution in the hydrogen embrittlement phenomenon of the present invention.

[0022] Figure 3This is the grazing incidence XRD spectrum of the hydrogen barrier layer in Example 1. The main phase of the hydrogen barrier layer is Ti4O7.

[0023] Figures 4 to 6 It is the cathode side glow discharge optical emission spectrum (GD-OES) chart of Examples 1 to 3.

[0024] Figure 7 This is the cathode side glow discharge optical emission spectrum (GD-OES) graph of Comparative Example 1. DETAILED DESCRIPTION

[0025] Those skilled in the art should recognize that the present embodiment is only used to illustrate the present invention, and is not used to limit the present invention. Any changes or modifications to the embodiment within the scope of the present invention are within the scope of the claims of the present invention.

[0026] Example 1

[0027] A 0.5 mm thick TA1 pure titanium bipolar plate is used as a titanium substrate, and a method for preparing a corrosion-resistant and hydrogen-embrittlement-resistant composite coating of a titanium substrate bipolar plate comprises the following steps: S1, titanium substrate pretreatment: the titanium substrate was polished step by step using 400-1200 grit sandpaper, and then mirror-polished using diamond polishing paste. Finally, the polished substrate was ultrasonically cleaned in acetone and ethanol for 15 min each, and then dried with cold air; S2, composite coating preparation: Ar + Ion glow etching to remove oxides and impurities on the substrate surface and activate the surface. + The glow etching bias voltage was set to -350 V, and the etching time was 30 min. High-power pulsed magnetron sputtering (HiPIMS) technology was used to deposit a titanium transition layer, a titanium suboxide hydrogen barrier layer, a titanium sealing layer, and a noble metal conductive layer on the surface of the titanium substrate in sequence: The preparation process parameters of the titanium transition layer are: constant power of 1kW, pulse duty cycle of 2%, deposition temperature of 200°C, substrate bias of -150V, deposition time of 2min; the coating deposition thickness is about 10nm; The preparation process parameters of the titanium suboxide hydrogen barrier layer are as follows: using Ti4O7 compound target as the sputtering target, the power supply is constant at 1.5kW, the pulse duty cycle is 5%, the deposition temperature is 200℃, the substrate bias voltage is -150V, the deposition time is 50min, and the coating deposition thickness is about 150nm; The preparation process parameters of the titanium sealing layer are: constant power of 1 kW, pulse duty cycle of 2%, deposition temperature of 200 °C, substrate bias of -150 V, deposition time of 2 min, and coating deposition thickness of about 10 nm. The preparation process parameters of the precious metal conductive layer are: using Pt target as the precious metal sputtering target, the power supply is constant at 1kW, the pulse duty cycle is 2%, the deposition temperature is 200°C, the substrate bias is -150V, the deposition time is 5min, and the coating deposition thickness is about 50nm.

[0028] The total thickness of the corrosion-resistant and hydrogen-embrittlement-resistant composite coating of the titanium substrate bipolar plate of Example 1 is about 220 nm.

[0029] Example 2

[0030] A 0.5 mm thick TA2 pure titanium bipolar plate is used as a titanium substrate, and a method for preparing a corrosion-resistant and hydrogen-embrittlement-resistant composite coating of a titanium substrate bipolar plate comprises the following steps: S1, titanium substrate pretreatment: the titanium substrate was polished step by step using 400-1200 grit sandpaper, and then mirror-polished using diamond polishing paste. Finally, the polished substrate was ultrasonically cleaned in acetone and ethanol for 15 min each, and then dried with cold air; S2, composite coating preparation: Ar + Ion glow etching to remove oxides and impurities on the substrate surface and activate the surface. + The glow etching bias voltage was set to -350 V, and the etching time was 30 min. The direct current magnetron sputtering (DCMS) technology was used to sequentially deposit a titanium transition layer, a titanium suboxide hydrogen barrier layer, a titanium sealing layer, and a noble metal conductive layer on the surface of the titanium substrate: The preparation process parameters of the titanium transition layer are as follows: deposition current of 1.5A, deposition temperature of 200°C, substrate bias of -100V, deposition time of 6min, and coating deposition thickness of about 30nm; The preparation process parameters of the titanium suboxide hydrogen barrier layer are: using Ti4O7 compound target as the sputtering target, deposition current of 2A, deposition temperature of 200°C, substrate bias voltage of -100V, deposition time of 30min, and coating deposition thickness of about 120nm; The preparation process parameters of the titanium sealing layer are as follows: deposition current of 1.5A, deposition temperature of 200°C, substrate bias of -100V, deposition time of 4min, and coating deposition thickness of about 20nm; The preparation process parameters of the noble metal conductive layer are: using Au target as the noble metal sputtering target, deposition current of 1.2A, deposition temperature of 200°C, substrate bias of -100V, deposition time of 4min, and deposition thickness of about 30nm.

[0031] The total thickness of the corrosion-resistant and hydrogen-embrittlement-resistant composite coating of the titanium substrate bipolar plate of Example 2 is about 200 nm.

[0032] Example 3

[0033] A 0.8 mm thick TA1 pure titanium bipolar plate is used as a titanium substrate, and a method for preparing a corrosion-resistant and hydrogen-embrittlement-resistant composite coating of a titanium substrate bipolar plate comprises the following steps: S1, titanium substrate pretreatment: the titanium substrate was polished step by step using 400-1200 grit sandpaper, and then mirror-polished using diamond polishing paste. Finally, the polished substrate was ultrasonically cleaned in acetone and ethanol for 15 min each, and then dried with cold air; S2, composite coating preparation: Ar + Ion glow etching to remove oxides and impurities on the substrate surface and activate the surface. + The glow etching bias voltage was set to -350V, and the etching time was 30min. First, a titanium transition layer and a titanium suboxide hydrogen barrier layer were deposited on the surface of the titanium substrate by high-power pulsed magnetron sputtering (HiPIMS) technology, and then a titanium sealing layer and a noble metal conductive layer were deposited on the surface of the hydrogen barrier layer by direct current magnetron sputtering (DCMS). The preparation process parameters of the titanium transition layer are: constant power of 1.2kW, pulse duty cycle of 3%, deposition temperature of 250°C, substrate bias of -150V, deposition time of 5min, and coating deposition thickness of about 20nm; The preparation process parameters of the titanium suboxide hydrogen barrier layer are as follows: using Ti4O7 compound target as the sputtering target, the power supply is constant at 1.2kW, the pulse duty cycle is 3%, the deposition temperature is 250℃, the substrate bias voltage is -150V, the deposition time is 30min, and the coating deposition thickness is about 100nm; The preparation process parameters of the titanium sealing layer are as follows: deposition current of 1.2A, deposition temperature of 200°C, substrate bias of -120V, deposition time of 2min, and coating deposition thickness of about 10nm; The preparation process parameters of the precious metal conductive layer are: using Pt target as the precious metal sputtering target, deposition current of 1.2A, deposition temperature of 200°C, substrate bias of -120V, deposition time of 4min, and deposition thickness of about 30nm.

[0034] The total thickness of the corrosion-resistant and hydrogen-embrittlement-resistant composite coating of the titanium-based bipolar plate of Example 3 is about 160 nm.

[0035] Comparative Example 1 Pretreatment of titanium substrate and Ar + The glow etching cleaning parameters are exactly the same as those in Example 1. A titanium transition layer and a noble metal conductive layer are sequentially deposited on the surface of the titanium substrate using high power pulsed magnetron sputtering (HiPIMS) technology: The preparation process parameters of the titanium transition layer are: constant power of 1kW, pulse duty cycle of 2%, deposition temperature of 200℃, deposition time of 3min. The thickness of the deposited coating is about 10nm; The preparation process parameters of the precious metal conductive layer are: using Pt target as the precious metal sputtering target, the power supply is constant at 1kW, the pulse duty cycle is 2%, the deposition temperature is 200°C, the substrate bias is -150V, the deposition time is 21min, and the deposition thickness is about 210nm.

[0036] The total coating thickness of the titanium substrate bipolar plate of Comparative Example 1 is about 220 nm.

[0037] The coated bipolar plate samples of Examples 1 to 3 and Comparative Example 1 were subjected to contact resistance test, corrosion performance test and bonding strength test respectively to evaluate the corrosion resistance and bonding strength performance of the coated samples. The corrosion test includes a dynamic potential polarization test (Tafel extrapolation method to determine the corrosion current density) and a 1.6V constant potential polarization test (to determine the contact resistance value before and after corrosion and the amount of ion precipitation in the corrosion solution); the corrosion solution is 0.5M H2SO4+0.1ppm HF, the holding time is 80°C, and the 1.6V constant potential polarization test duration is 24h.

[0038] According to GB / T 20042.6-2011 "Proton Exchange Membrane Fuel Cell Part 6: Bipolar Plate Characteristics Test Method", the contact resistance with carbon paper is tested under 2.4MPa pressure.

[0039] The 24h constant potential polarization ion precipitation amount is measured and calculated by ICP-MS using a professional third-party organization.

[0040] The coating adhesion was tested according to the 100-grid method of GB / T 9286-2021. The test results are shown in Table 1.

[0041] Table 1 Test results of Examples 1 to 3 and Comparative Example 1 Test items Example 1 Example 2 Example 3 Comparative Example 1 <![CDATA[Corrosion current density (μA / cm 2 )]]> 2.79 3.26 3.10 3.47 <![CDATA[Contact resistance with carbon paper before corrosion (mΩ·cm 2 )]]> 1.21 1.17 1.19 1.09 <![CDATA[Contact resistance with carbon paper after corrosion (mΩ·cm 2 )]]> 1.52 1.63 1.59 1.48 <![CDATA[Total precipitation amount of Pt / Au / Ti per unit area (μg / cm 2 )]]> <0.05 <0.05 <0.05 <0.05 Coating adhesion (100-grid test) Level 0 Level 0 Level 0 Level 0 Currently, there is no unified standard performance index in the field of PEM water electrolysis. Referring to the index requirements of bipolar plates of the U.S. Department of Energy (DOE) in the field of fuel cells, by 2025, the contact resistance between the bipolar plate and the carbon paper should be less than 10mΩ·cm 2 From the test results in Table 1, it can be seen that although the composite coatings of Examples 1 to 3 reduce the precious metal loading, resulting in a slightly higher contact resistance with carbon paper before and after corrosion than the pure precious metal coating, the difference is not obvious and is still far below 10 mΩ·cm 2 It meets the standards of the pure precious metal coating and has the same conductive corrosion resistance and coating adhesion as the pure precious metal coating. Therefore, it effectively reduces the coating processing cost without sacrificing the conductive corrosion resistance.

[0042] The titanium-based bipolar plates of Examples 1 to 3 and Comparative Example 1 were respectively installed in the grooves for a 1000-hour durability test, and then the cathode side glow discharge optical emission spectroscopy (GD-OES) test was performed to characterize the change of hydrogen element signal intensity with coating depth to evaluate the hydrogen penetration, that is, its anti-hydrogen embrittlement performance. The results are shown in Figures 4 to 7 . It can be clearly seen that in Examples 1 to 3, the H element is effectively blocked and does not enter the titanium substrate. The detected H signal is only the impurity component in the metal, and the coating has excellent hydrogen embrittlement resistance. In Comparative Example 1, due to the lack of a hydrogen barrier layer, the relatively thick precious metal layer cannot block the penetration of the H element. H penetrates the coating into the titanium substrate and dissolves inside the titanium substrate. The detected H signal is strong and exists stably within a certain depth range of the titanium substrate. The coating has poor hydrogen embrittlement resistance. It is proved that the composite coatings of Examples 1 to 3 of the present invention have excellent hydrogen embrittlement resistance.

Claims

1. A corrosion-resistant and hydrogen-embrittlement-resistant composite coating for titanium-based bipolar plates, characterized in that: A titanium transition layer, a titanium suboxide hydrogen barrier layer, a titanium sealing layer and a noble metal conductive layer are sequentially coated on the surface of the titanium substrate; the titanium transition layer is a single titanium layer with a thickness of 10 to 30 nm; the material of the titanium suboxide hydrogen barrier layer is a material with a molecular formula of Ti n O 2n-1 The Magneli phase titanium suboxide with 4≤n≤10 has a thickness of 100-150nm; the titanium sealing layer is a single titanium layer with a thickness of 10-50nm; the material of the precious metal conductive layer is at least one of platinum, gold, ruthenium and iridium, with a thickness of 20-50nm.

2. The corrosion-resistant and hydrogen-embrittlement-resistant composite coating for titanium-based bipolar plates according to claim 1, characterized in that: The Magneli phase titanium oxide is Ti4O7, Ti5O9, Ti6O 11 One or more of the following.

3. The corrosion-resistant and hydrogen-embrittlement-resistant composite coating for titanium-based bipolar plates according to claim 1, characterized in that: The total thickness of the corrosion-resistant and hydrogen-embrittlement-resistant composite coating is 160 to 260 nm.

4. The corrosion-resistant and hydrogen-embrittlement-resistant composite coating for titanium-based bipolar plates according to claim 1, characterized in that: The titanium substrate bipolar plate is one of a pure titanium flat plate with a metal stretching / stamping mesh, a pure titanium plate with an etched flow channel, and a stamped pure titanium bipolar plate.

5. The corrosion-resistant and hydrogen-embrittlement-resistant composite coating for titanium-based bipolar plates according to claim 4, characterized in that: The titanium-based bipolar plate is made of pure titanium material labeled TA1 or TA2, and has a thickness of 0.5 to 2 mm.

6. The method for preparing the corrosion-resistant and hydrogen-embrittlement-resistant composite coating for titanium substrate bipolar plates according to any one of claims 1 to 5, characterized in that: The steps include: S1, titanium substrate pretreatment: firstly, the titanium substrate is polished step by step, then mirror polished, then ultrasonically cleaned in acetone and ethanol respectively, and dried with cold air; S2, preparation of composite coating: depositing a titanium transition layer, a titanium suboxide hydrogen barrier layer, a titanium sealing layer and a noble metal conductive layer on the surface of the titanium substrate in sequence.

7. The method for preparing the corrosion-resistant and hydrogen-embrittlement-resistant composite coating for titanium substrate bipolar plates according to claim 6, characterized in that: The step-by-step grinding uses 400-1200 mesh sandpaper, and the mirror polishing uses diamond grinding paste.

8. The method for preparing the corrosion-resistant and hydrogen-embrittlement-resistant composite coating for titanium substrate bipolar plates according to claim 6, characterized in that: The preparation process of the composite coating comprises one or more of magnetron sputtering, multi-arc ion plating and / or electron beam evaporation.

9. The method for preparing the corrosion-resistant and hydrogen-embrittlement-resistant composite coating for titanium substrate bipolar plates according to claim 8, characterized in that: The power output mode of the magnetron sputtering is one or more of direct current, direct current pulse and / or high power pulse; the titanium transition layer and the titanium sealing layer use titanium metal single target as sputtering target; the sub-titanium oxide hydrogen barrier layer uses Magneli phase sub-titanium oxide target as sputtering target; the noble metal conductive layer uses noble metal single target as sputtering target.

10. The method for preparing the corrosion-resistant and hydrogen-embrittlement-resistant composite coating for titanium substrate bipolar plates according to claim 6, characterized in that: Before the composite coating is deposited, the surface of the titanium substrate needs to be etched with glow plasma, wherein the main component of the glow plasma is Ar ions, and the etching time is 20 to 60 minutes.

Citation Information

Patent Citations

  • Titanium material, separator, solid high-polymer fuel cell, and titanium-material manufacturing method

    CN107408710A

  • Preparation method of corrosion-resistance and high-electroconductibility composite coating for electrode

    CN109402586A

  • Titanium-based titanium oxide bipolar plate and preparation method thereof

    CN110071302A

  • Conductive pre-coating layer for titanium polar plate of fuel cell and preparation method of conductive pre-coating layer

    CN115332552A

  • Composite coating, bipolar plate and water electrolysis device

    CN115710713A

Cited By

  • Metal compound coating, preparation method thereof and modified bipolar plate

    CN119592987A

  • Porous transmission layer for proton exchange membrane water electrolysis cell as well as preparation method and application of porous transmission layer

    CN122522276A

  • A porous transport layer for a proton exchange membrane water electrolyser and methods of making and using the same

    CN122522276B

  • Method for treating a porous transport layer and coated transport layer

    WO2026125627A3

  • Method for treating a structural component of an electrochemical cell and coated structural component

    WO2026125633A3